Kepemimpinan yang Hidup dalam Kristus: (Studi Tentang Visi, Integritas, dan Passion Berdasarkan Yohanes 15:1 8,13 17) - Gunawan Simondinata; Rita Widjaja (Pusat Riset dan Inovasi Nasional, 2026)
Christian leadership rooted in John 15:1 8 and 13 17 depicts Jesus as the true vine, where leaders, as branches, must abide (remain attached) in Him (Jesus Christ) to bear abundant fruit through divine vision, moral integrity, and passionate service. This analysis explores how the vine metaphor shapes a leadership model that depends on an intimate (attached) relationship with Christ, producing fruit in daily life and ministry. The relationship between the vine and the branches reflects the necessity for church leaders to rely on Christ for guidance, strength, and the ability to serve others effectively. The model emphasizes the importance of nurturing personal spiritual growth, cultivating virtues that align with God’s purpose, and fostering a ministry focused on service and integrity. These principles are relevant for Indonesian church leaders who are called to integrate their faith with contextual ministry. By examining the passage through exegesis and literature review, this article provides insights on developing a Christ centered approach to leadership.